Pengaruh Kemampuan Membaca Al-Qur’an Dan Konsep Diri Siswa terhadap Hasil Belajar Aqidah Akhlak - Munawiroh Munawiroh (Badan Litbang dan Diklat Kementerian Agama RI, 2011)
AbstractThis research is performed by the student at Grade XI of the Islamic State Senior High School of South Jakarta, in the odd semester for the academic year 2009-2010. The research sample is the student at grade XI at three Islamic State Senior High Schools in South Jakarta. A data collection is performed by a causal survey with lane analysis technique and using a relation test on causative with exploratory, i.e, track analysis. This research outcome explains that; 1) the students who are capable of (understanding or comprehending, rading letters with proper spelling in accordance with principles and able to interpret either in linguistic or psycholinguistic manner) reading Qur’an which is proven to acquire a satisfied score for the lesson of Moral Faith; 2) the students who have well-self concept (skill and capability) is proven to hoghly influence on the learning outcome of the Moral Faith; and 3) the students who are capable of reading the Qur’an well is proven to be highly influenced by a true self-concept of the students. AbstrakPenelitian ini dilakukan pada siswa kelas XI Madrasah Aliyah Negeri Jakarta Selatan, pada semester ganjil tahun ajaran 2009-2010. Sampel penelitian adalah siswa kelas XI di tiga Madrasah Aliyah Negeri di Jakarta Selatan. Pengumpulan data dilakukan dengan survei kausal dengan teknik analisis jalur dan menggunakan uji hubungan sebab akibat dengan eksploratori, yaitu analisis jalur. Hasil penelitian ini menjelaskan bahwa; 1) siswa yang mampu (mengerti ata memahami, melafalkan huruf-huruf dengan makhraj huruf yang sesuai dengan kaidah-kaidah dan dapat menginterpretasikan baik secara linguistik maupun psykolinguistik) membaca al-Qur’an terbukti memperoleh nilai yang memuaskan pada pelajaran Aqidah Akhlak; 2) siswa yang memiliki konsep diri matang (keteampilan dan kecakapan) terbukti sangat berpengaruh terhadap hasil belajar Aqidah Akhlak; dan 3) siswa yang mampu membaca al-Qur’an dengan baik terbukti sangat dipengaruhi oleh konsep diri siswa yang benar-benar matang.